Quinolones-Induced Musculoskeletal, Neurological, and Psychiatric ADRs: A Pharmacovigilance Study Based on Data From the Italian Spontaneous Reporting System - Scavone, Cristina; Mascolo, Annamaria; Ruggiero, Rosanna; Sportiello, Liberata; Rafaniello, Concetta; Berrino, Liberato; Capuano, Annalisa (Frontiers in Pharmacology, 2020)
Background: The use of quinolones has been associated with the development of serious and persistent adverse drug reaction mainly affecting muscles, joints and the nervous system. This risk has led the European Medicines Agency (EMA) to endorse some restrictions on the use of this class of antibiotic. Therefore, we performed a study to primary estimate the reporting probability of musculoskeletal, neurological, and psychiatric adverse drug reactions (ADRs) among quinolone generations using national data. Methods: We retrieved Individual Case Safety Reports (ICSRs) with a quinolone as suspected drug among those reported through the Campania spontaneous reporting system from January 1st, 2001 to April 30th. Moreover, we retrieved national aggregated safety data from the online public report system (RAM system) for the period from January 1st, 2002 to March 31st, 2019. Risk factors were classified as “age greater than 60 years”, “therapeutic indication”, “renal failure”, “organ transplantation”, “use of corticosteroid”, and “history of side effects”. Reporting odds ratio (ROR) was computed to evaluate the reporting probability of musculoskeletal, neurological or psychiatric events among quinolones generations. Results: A total of 87 ICSRs with a quinolone as suspected drug that reported at least one musculoskeletal, neurological, and psychiatric adverse event were identified in the Campania spontaneous reporting system. Forty-nine (56.3%) ICSRs reported risk factors (total risk factors: 59). The most reported risk factor was “age greater than 60 years” (69.5%), followed by “therapeutic indication” (16.9%), “renal failure” (5.1%), “organ transplantation” (3.4%), “use of corticosteroid” (3.4%), and “history of side effects” (1.7%). Second-generation quinolones were associated with a lower reporting probability of musculoskeletal (ROR 0.70; 95%CI 0.63-0.79), neurological (ROR 0.81; 95%CI 0.73-0.90), and psychiatric (ROR 0.55; 95%CI 0.44-0.63) ADRs compared to the third generation of quinolones. Conclusions: Our findings showed that third-generation quinolones were always associated with a higher reporting probability of musculoskeletal, neurological and psychiatric ADRs compared to the second generation ones. Moreover, we described risk factors in more than half of our cases suggesting that the inappropriate use of quinolones is a phenomenon that may frequently predispose patients to the occurrence of these ADRs.